Smart Wall Model for Molecular Dynamics Simulations of Nanoscale Gas Flows (Communications in Computational Physics, 2010)
Three-dimensional molecular dynamics (MD) simulations of gas flows con-fined within nano-scale channels are investigated by introduction of a smart wall modelthat drastically reduces the memory requirements of MD simulations for gas flows.The smart wall molecular dynamics (SWMD) represents three-dimensional FCC wallsusing only 74 wall molecules. This structure is kept in the memory and utilized foreach gas molecule surface collision. Linear Couette flow of argon at Knudsen number10 is investigated using the SWMD utilizing Lennard-Jones potential interactions. Effectsof the domain size on the periodicity boundary conditions are investigated usingthree-dimensional simulations. Domain sizes that are one mean-free-path long in theperiodic dimensions are sufficient to obtain domain-size independent MD solutions ofnano-scale confined gas flows. Comparisons between the two- and three-dimensionalsimulations show the inadequacy of two-dimensional MD results. Three-dimensionalSWMD simulations have shown significant deviations of the velocity profile and gasdensity from the kinetic theory based predictions within the force penetration regionof the walls.